IC 9414 Thermal Characteristics Of Reeled Trailing Cables For Shuttle Cars - P. G. Kovalchik (The National Institute for Occupational Safety and Health (NIOSH), 1994)
Safe electrical operation of shuttle cars depends upon maintaining the trailing cable's conductor temperature below 90° C. However, trailing cables are wound on and off reels, which changes the heat transfer characteristics of the cable-reel system. Derating factors for trailing cables are an attempt to adjust for this changing heat transfer mechanism in a practical way. The U.S. Bureau of Mines conducted research to determine acceptable derating factors for reeled mine trailing cables, using four cable-reel combinations, representative of industry usage. Cables were continuously and intermittently loaded at different duty cycles with direct currents of different magnitudes. Relationships between the average temperature rise and current load were established for each layer of each cable. Two models were constructed; one used empirical data from the continuous and intermittent load tests, and the other was based on thermodynamic theory. Results obtained from the theoretical model were compared with those from the empirical model for the rated temperature rise of the cable. Both models can be used to simulate a variety of test conditions including those that normally cannot be conducted in the laboratory. This information was used to determine acceptable derating factors for each layer of these cable-reel combinations.